Dual‐Functional Poly(3, 4‐ethylenedioxythiophene)/MnO2 Nanoellipsoids for Enhancement of Neurite Outgrowth and Exocytosed Biomolecule Sensing in PC12 Cells. (2nd November 2012) - Kim, Sojin; Oh, Wan‐Kyu; Jeong, Yoon Seon; Jang, Jyongsik
Abstract Dual‐functional MnO2‐decorated poly(3, 4‐ethylenedioxythiophene) (PEDOT/MnO2) nanoellipsoids are fabricated for enhancement of neurite outgrowth during differentiation and real‐time monitoring of PC12 cells. The PEDOT nanoellipsoids are prepared by chemical oxidation polymerization in reverse microemulsion and the MnO2 domains on the surface of the PEDOT are formed by redox deposition. A PC12 cell is used as a model cell for neuronal differentiation. The morphology, differentiation efficiency, average neurite length, expression level of DMT1, phosphorylation of ERK1/2, and viability of PC12 cells upon the exposure of the PEDOT/MnO2 nanoellipsoids are examined. The PEDOT/MnO2 nanoellipsoids facilitate neurite outgrowth in proportion to the dose of the nanoellipsoids, and MnO2 domains play a pivotal role in facilitation effects on cell differentiation. The PEDOT/MnO2 nanoellipsoids represent low toxicity in the cells due to biocompatible PEDOT matrix. Moreover, the PEDOT/MnO2 nanoellipsoids are further applied as a transducer material for label‐free real‐time monitoring of PC12 cells. The exocytosed catecholamines from living cells are successfully detected. The dual‐functionalized PEDOT/MnO2 nanoellipsoids may be used in tissue engineering related to the development and monitoring of mammalian nervous systems.